Penerapan Metode Pembelajaran Joyfull Learning Berbasis Ice Breaking Dalam Meningkatkan Keaktifan dan Hasil Belajar Siswa pada Mata Pelajaran Fiqih di Kelas VIII Mts Hubbulwathan Duri Riau - Intan Nurbaiti; Bambang Trisno; Herdalina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the application of a fun ice breaking based method in increasing studentactivity and learning outcomes in fiqh class VIII at MTSS Hubbulwathan Duri, Riau. The application ofthis method is expected to be a solution to overcome problems in the world of education. This study uses aclass action research (CAR) method with a collaborative PTK type and uses the Kemmis and MC models.Taggart. PTK stages consist of: Planning, Implementation, Observation and Reflection. The results ofapplying the joyl method based on ice breaking in fiqh subjects in cycle 1 on student activity get 60%active student results and in cycle 2 get 100% active student results, the increase in student activity fromcycle 1 to cycle 2 is 40% . Then in the learning outcomes in cycle 1 students who achieve KKM reach65% and cycle 2 students who achieve KKM reach 100%. So the increase in student learning outcomesfrom cycle 1 to cycle 2 increased by 35%. Thus that the application of the ice breaking-based joy learningmethod in fiqh subjects experienced an increase in student activity and learning outcomes.